Implementation of a managed care programme in Germany using the example of the Baden-Wuerttemberg contract on care in the field of cardiology: PhD thesis summary - Hennrich, Patrick (International journal of integrated care, 2022)
This thesis analysed the implementation of the German medical specialists’ contract in cardiology, a managed care programme within the state of Baden-Wuerttemberg. Research focused on exploring differences between participating and non-participating physicians, their motivation to participate, actual implementation of the programme and its perceived effects. Mixed methods consisting of questionnaires and qualitative telephone interviews with cardiologists and general practitioners showed that participants were older than non-participants, participation was mainly financially driven and implementation was successful regarding medical aspects, but less so regarding patient services and communication between providers. The majority of physicians in the study perceived little to no impact of the programme on quality and efficiency of cardiology care. Still, they saw their expectations fulfilled.